Fibrillin gene family and its role in plant growth, development, and abiotic stress - El-Sappah, Ahmed H.; Li, Jia; Yan, Kuan; Zhu, ChaoYang; Huang, Qiulan; Zhu, Yumin; Chen, Yu; El-Tarabily, Khaled A.; AbuQamar, Synan F. (Frontiers in Plant Science, 2024)
Fibrillins (FBNs), highly conserved plastid lipid-associated proteins (PAPs), play a crucial role in plant physiology. These proteins, encoded by nuclear genes, are prevalent in the plastoglobules (PGs) of chloroplasts. FBNs are indispensable for maintaining plastid stability, promoting plant growth and development, and enhancing stress responses. The conserved PAP domain of FBNs was found across a wide range of photosynthetic organisms, from plants and cyanobacteria. FBN families are classified into 12 distinct groups/clades, with the 12 th group uniquely present in algal-fungal symbiosis. This mini review delves into the structural attributes, phylogenetic classification, genomic features, proteinprotein interactions and functional roles of FBNs in plants, with a special focus on their effectiveness in mitigating abiotic stresses, particularly drought stress.